2020
DOI: 10.1155/2020/6663291
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Derived Semaphorin 4D Induces Inflammatory Cytokine Production of Endothelial Cells via Different Plexin Receptors in Kawasaki Disease

Abstract: Inflammation of endothelial cells (ECs) plays an important role in the pathogenesis of coronary artery lesions (CALs) in Kawasaki disease (KD). Semaphorin 4D (Sema4D) is the first semaphorin shown to have immunoregulatory functions by interacting with its receptors—plexin Bs. Recently, Sema4D has been reported to exert a proinflammatory effect on the endothelium and to be involved in cardiovascular disease. However, the role of Sema4D in KD remains unknown. This study was aimed at revealing the change of solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…In this study, we also found that albumin concentrations were decreased in the KD group, indicating these KD patients presented a status of vascular leakage. Sera from patients with KD have recently been used as a stimulator to achieve KD vasculitis in vitro [ 12 , 16 18 ]. KD serum can induce dysfunction and inflammation of HCAECs by activating Ca2+/nuclear factor of activated T cell signaling pathway, which leads to the proliferation and angiogenesis of endothelial cells [ 16 ]; and in our previous study, we showed that sera from KD patients can stimulate HCAECs to upregulate some cell-membrane molecules, such as plexin Bs [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we also found that albumin concentrations were decreased in the KD group, indicating these KD patients presented a status of vascular leakage. Sera from patients with KD have recently been used as a stimulator to achieve KD vasculitis in vitro [ 12 , 16 18 ]. KD serum can induce dysfunction and inflammation of HCAECs by activating Ca2+/nuclear factor of activated T cell signaling pathway, which leads to the proliferation and angiogenesis of endothelial cells [ 16 ]; and in our previous study, we showed that sera from KD patients can stimulate HCAECs to upregulate some cell-membrane molecules, such as plexin Bs [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sera from patients with KD have recently been used as a stimulator to achieve KD vasculitis in vitro [ 12 , 16 18 ]. KD serum can induce dysfunction and inflammation of HCAECs by activating Ca2+/nuclear factor of activated T cell signaling pathway, which leads to the proliferation and angiogenesis of endothelial cells [ 16 ]; and in our previous study, we showed that sera from KD patients can stimulate HCAECs to upregulate some cell-membrane molecules, such as plexin Bs [ 12 ]. Here, for the first time, we treated HCAEC monolayers with KD sera and investigated the effect of KD sera on EC permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their role as receptors for immune guidance molecules has recently been identified. Reports indicate that Type-B plexins are abundant in lung epithelium [ 16 ], and their activation induces pro-inflammatory cytokine production [ 17 , 18 ]. Although the exact mechanism is unclear, it is thought that Rnd1 interaction with plexin-B1 regulates Rho GTPases either through their intrinsic RhoGAP activity or through PDZ-RhoGEF to induce cytokine expression [ 15 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the expression of Sema4D disturbs the cellular function of CD15+ neutrophils and correlates with the shedding proteinase, ADAM17, which interacts with endothelial cells and is associated with cardiovascular disease. Sema4D also promotes the production of cytokines in HCAECs in a dose-dependent manner through the Sema4D-plexin B axis ( 35 ) ( Figure 1 ).…”
Section: Molecular Mechanism Of Vascular Endothelial Cell Injury and ...mentioning
confidence: 99%